Some Possibilities To Influence Capacity, Energy Consumption And Product Quality In Iron Ore Sintering - 1. Introduction - Ottmar Burghardt (Society for Mining, Metallurgy & Exploration, 1982)
Sintering of iron ore has undergone a dramatic development world-wide. Today, the annual world production amounts to approximately 600 million tons. At present, the sintering process in competition with pelletizing, seems to offer certain advantages inasmuch as it allows the use of solid fuels. Also, its charging behaviour in the blast furnace is, in general, considered as being better than that of pellets. This is true, in particular, for the charging behaviour and the gas permeability in relation to the grain size. Moreover, instead of charging limestone into the blast furnace, for instance, the basic components which are necessary for the burden materials can generally be supplied in a simpler and more cost-effective way by using basic sinter instead of basic pellets. While in sintering, with basicity rising to the range of 1.6 to 1.8 CaO : SiO2, the capacity increases and the sinter quality shows improvements in most of its characteristics, the pro¬duction of basic pellets generally requires a higher fuel rate, when compared to acid pellets, while production capacity decreases and some of the quality characteristics deteriorate.